CFD simulations to improve air distribution inside cold climate broiler houses involving heat exchangers. (October 2020) - Coulombe, Frédéric; Rousse, Daniel R.; Paradis, Pierre-Luc
Abstract : Propane heating is both a financial and an environmental burden for broiler houses located in cold climate regions. Heat recovery can reduce propane consumption significantly, by preheating fresh air inflow with stalled air outflow. While there have been many studies on the improvement of broiler houses direct ventilation, little attention has been given to the integration of heat exchangers. In this study, an existing broiler house (800 m 2 ) equipped with two air-to-air ductless heat exchangers (0.38 m 3 s -1 each) was simulated. Computational fluid dynamics (CFD) software OpenFOAM was used to create a 3D steady-state buoyant simulation with RNG k - ε turbulence model. The CFD model was validated with experimental data from Nielsen (1976). In the reference configuration, the two heat exchangers were aligned in parallel, positioned against the northern wall. Three alternative heat exchangers configurations were simulated and analysed in their ability to provide adequate, uniform velocity, temperature and air age at bird height. No configuration was found to avoid excessive air velocities entirely. One configuration (C1) reduced the air age standard deviation from 477 to 179 s. It also increased the surface with adequate air quality from 55% (C0, reference case) to 72% of the floor area. Despite using the same heating power, temperature differences of up to 2 °C were observed in the mean air temperature of broiler zones of different configurations. These results confirm that ventilation performance can be improved by a careful analysis of heat exchangers position and its effects on airflow patterns. Highlights: Heat exchangers save fuel but achieving uniform housing conditions is a challenge. One configuration (C1) reduced the air age standard deviation from 477 to 179 s. Secondary vortex with low air quality can form with some configurations. Excessive wind chill seems hard to eliminate with ductless heat exchangers.